Synthesis and Characterization of Some New Benzothiazine, Dihydroquinazolinone and Oxazepine Derivatives from 1, 8-Naphthalic Anhydride and Evaluation of Their Antimicrobial Activity - Mohammed G. A Al-Khuzaie (Journal of Global Pharma Technology, 2018)
New benzothiazine, hydroquinazolinone, and oxazepine derivatives had been synthesized from the reaction of 1, 8-naphthalic anhydride with p-phenylenediamine to give 1,8-naphthalimide derivative (1), which in turn react with a number of aromatic aldehydes to give Schiff bases derivatives (2-7) that reacted with three different reagents (2-mercaptobenzoic acid, anthranilic acid and phthalic anhydride) respectively to form benzothiazine (8-13), dihydroquinazolinone (14-19) and oxazepine (20-25) derivatives, respectively. The structures of synthesized derivatives were characterized by [13C-NMR, 1H-NMR, and FTIR] and measuring of characteristic physical properties and specific reactions. Moreover, the biological effect of some of preparing compounds was tested on fungicidal and some of bacteria.Keywords: 1, 8-naphthalic anhydride, benzothiazine, hydroquinazolinone, oxazepine, anti-microbial activity.